Characterization of Begomovirus and Potyvirus causing mixed infections on chili plant (Capsicum frutescens L.) in South Lampung, Indonesia - Helina, Selvi; Nurfadillah, Fauziah Rizky; Hasriadi Mat Akin; Nurdin, Muhammad; Purnomo; Lestari, Puji (Agriculture and Natural Resources, 2026)
Importance of the work: Chili (Capsicum frutescens L.) productivity in Indonesia is threatened by mixed virus infections that complicate diagnosis and control Objectives: To characterize viruses associated with symptomatic C. frutescens plants in South Lampung using molecular techniques. Materials and Methods: DNA and RNA were extracted from infected samples and subjected to polymerase chain reaction amplification using specific primers targeting Begomovirus and Potyvirus. Sequencing was followed by homology analysis using the Basic Local Alignment Search Tool. In addition, phylogenetic analysis was conducted and pathogenicity tests were performed on healthy chili plants. Results: The presence was confirmed of both Begomovirus and Potyvirus in the analyzed samples, with no amplification detected for specific primers of Cucumber mosaic virus or Tobacco Infectious Chlorosis Virus. The Begomovirus isolate shared 93% identity with Pepper Yellow Leaf Curl Virus from Kertha, Indonesia. The Potyvirus isolate had 100% identity with Potato Virus Y from Ukraine. Phylogenetic analysis confirmed these relationships. The pathogenicity tests identified symptoms ranging from mild to severe mosaicing, leaf curling and chlorosis. Main finding: The occurrence was confirmed of mixed infections involving Begomovirus and Potyvirus in C. frutescens from South Lampung, Indonesia and highlighted the importance of molecular diagnostics in understanding virus diversity and supporting disease control strategies.